2018
DOI: 10.1371/journal.pone.0209666
|View full text |Cite
|
Sign up to set email alerts
|

Do young black men who have sex with men in the deep south prefer traditional over alternative STI testing?

Abstract: BackgroundHigh sexually transmitted infection (STI) rates in the South, especially among young black men who have sex with men (YB MSM), make STI testing imperative for public health.PurposeTo identify STI testing preferences in this population to improve testing delivery and utilization.MethodsYB MSM ages 16–35 in Birmingham, Alabama participated in focus groups (FG). A trained qualitative researcher coded transcripts after each FG and added questions to explore emerging themes.ResultsBetween September 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Convenience was a key attribute for MSM who preferred home self-sampling [ 14 , 15 ] or self-testing [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table 1 ). A study conducted in the UK used focus groups and interviews with 44 MSM to explore the acceptability of home self-sampling kits [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Convenience was a key attribute for MSM who preferred home self-sampling [ 14 , 15 ] or self-testing [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table 1 ). A study conducted in the UK used focus groups and interviews with 44 MSM to explore the acceptability of home self-sampling kits [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After completing the questionnaire participants provided an email address to study staff, were sent a link to a password protected Zoom meeting, and were informed of the time and date of their 60-minute VFG session. All VFGs were facilitated by the same moderator (author E.L.A), who has extensive experience in qualitative research involving sexual and gender minorities [ 23 25 ]. Each VFG was audio and video recorded via the Zoom platform.…”
Section: Methodsmentioning
confidence: 99%
“…Before this study, we conducted focus groups exploring HIV/STI testing preferences among YBMSM in Birmingham, AL (n = 36). 23 Participants not only preferred physician-performed HIV/STI testing at doctors' offices but also having multiple options for testing locations and timing. Participants did not prefer nonphysician staff or at-home self-testing.…”
mentioning
confidence: 99%